National and Cultural Identity in Iraq in the Face of the Formation of the New Order in the Middle East. Philosophical Reflection and the Political Reality - Warsza, Paulina Jagoda (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
After Arab Spring many hopes were dashed. However historical change must be happening now in the area of social awareness. The rise of extremism limits awareness and also endangers the Arab identity. The Arab revolution has to be more than the overthrowing of dictators. Bennabi created the concept of Post- Almohad Man and its “Colonsability” – a tendency to be colonized which allows the aggressor to be transformed into the colonizer. Is Bennabi’s theory applicable to Iraq? Should killing a Post- Almohad Man be the aim, as Bennabi postulated, and only this will allow society to develop? Although Bennabi rather had in mind liberation from auto-stereotype and reconstruction of identity, many still interpret his words literally.